Actividades de recreación infantil para el desarrollo del área motriz gruesa de los niños(as) de 1 a 2 años de edad del centro de estimulación y desarrollo infantil El Castillo Encantado de la ciudad de Loja, periodo peptiembre 2013 – julio 2014 - Armijos Ortiz, Sandra Jackeline (2015)
The Children's Recreational Activities Guide aims to prepare children so that they are able to learn, solve problems, and use their knowledge in everyday life.. Considering this a matter of great importance in our country, this city and town has seen fit to research: CHILDREN'S RECREATIONAL ACTIVITIES DRIVE FINE MOTOR DEVELOPMENT OF CHILDREN (AS) OF 1 TO 2 YEARS OLD BY THE CENTRO DE ESTIMULACIÓN Y DESARROLLO INFANTIL “EL CASTILLO ENCANTADO” of the city of Loja from SEPTEMBER 2013 to JULY 2014. The five objectives related to this topic include analyzing the theoretical foundation of the Children's Recreation Area and Fine Motor skills .This social intervention work utilized both theoretical and practical methods: analysis, synthesis, description, hermeneutics. The technique used was a structured questionnaire with 5 items aimed at teachers for use with children to demonstrate the comprehensive development of the children. As socio affective instrument, the EAD-Nelson Ortiz was used. There were 13 children in the test sample and 2 teachers from the Centro de Estimulación y Desarrollo Infantil “El Castillo Encantado”. As for the results of the data analysis, it can be said that teachers need a little more knowledge and initiative in terms of children's recreational activities. Most children were found to be at the Medium High level, which concluded that the children's recreational activities were very helpfull for the development of the Department of Fine Motor Skills in children of 1-2 years old.